2012
DOI: 10.1089/vbz.2011.0688
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Leishmania mexicana in a Cutaneous Leishmaniasis Case in Sinaloa, Mexico

Abstract: Leishmaniasis has been considered endemic in Sinaloa, Mexico, since 1994. Despite that Leishmania mexicana is the main etiological agent of cutaneous leishmaniasis (CL) in other regions of Mexico, the species causing CL in patients from Sinaloa state has not been previously established, although Leishmania braziliensis has been found in the neighboring southern state, Nayarit. L. braziliensis is also associated with mucocutaneous leishmaniasis, which is a more complicated clinical variant. Due to the implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…In Mexico, Pérez-Vega et al [19] in Durango State and Ochoa-Diaz et al [20] in Sinaloa State identified Leishmania mexicana in clinical samples with ITS1 PCR RFLP assay.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, Pérez-Vega et al [19] in Durango State and Ochoa-Diaz et al [20] in Sinaloa State identified Leishmania mexicana in clinical samples with ITS1 PCR RFLP assay.…”
Section: Discussionmentioning
confidence: 99%
“…Concerniente a las especies parásitas, la literatura disponible es amplia e incluye aspectos del ámbito médico (Velasco-Castrejón et al, 1997Becerril et al, 2010), inmunológico (Espinoza et al, 2011), serológicos (Goldsmith et al, 1979;Becerril-Flores y Valle-De la Cruz, 2003;Salazar et al, 2007;Galavíz-Silva et al, 2009), endemismo (Ramos-Ligonio et al, 2010), prevalencia (Sánchez-Vega et al, 2000) y aspectos moleculares (Pérez-Mutul et al, 1994;Ochoa-Díaz et al, 2012). Con un enfoque particular hacia los kinetoplástidos, Bautista-López (1993), de Haro (1997)…”
Section: Biodiversity Of Protists (Heterotrophic Flagellates) In Mexicounclassified
“…In Mexico, Leishmania infantum, L. braziliensis, and L. mexicana have been reported as the causative agents of human leishmaniasis (Sanchez-Tejeda et al 2001, Pérez-Vega et al 2009, Ochoa-Diaz et al 2012, and the last two species are primarily responsible for MCL and CL lesions, respectively. CL is the major endemic form of the disease and has spread across 17 states in Mexico, whereas VL has been found in only two states, Guerrero and Morelos, and MCL has also been reported in two states, Tabasco and Chiapas (World Health Organization 2010, Pérez-Vega et al 2009, Ochoa-Diaz et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical forms of leishmaniasis include cutaneous leishmaniasis (CL; localized or diffuse), which is characterized by ulcerative lesions on the skin; mucocutaneous leishmaniasis (MCL), which results in destruction of mucosal tissue; and visceral leishmaniasis (VL, or Kala-Azar), which affects various organs and is potentially lethal (Salotra et al 2005, Reithinger et al 2007, World Health Organization 2010, Stockdale et al 2013. In Mexico, Leishmania infantum, L. braziliensis, and L. mexicana have been reported as the causative agents of human leishmaniasis (Sanchez-Tejeda et al 2001, Pérez-Vega et al 2009, Ochoa-Diaz et al 2012, and the last two species are primarily responsible for MCL and CL lesions, respectively. CL is the major endemic form of the disease and has spread across 17 states in Mexico, whereas VL has been found in only two states, Guerrero and Morelos, and MCL has also been reported in two states, Tabasco and Chiapas (World Health Organization 2010, Pérez-Vega et al 2009, Ochoa-Diaz et al 2012.…”
Section: Introductionmentioning
confidence: 99%